A Fast Fragility Analysis Method for Seismically Isolated RC Structures - Cholap Chong; Mufeng Chen; Mingming Wang; Lushun Wei (Buildings, 2025)
This paper presents an advanced seismic performance evaluation of reinforced concrete (RC) seismically isolated frame structures under the conditions of rare earthquakes. By employing an elastic–plastic analysis in conjunction with a nonlinear multi-degree-of-freedom model, this study innovatively assesses the incremental dynamic vulnerability of isolated structures. A novel equivalent linearization method is introduced for both single- and two-degree-of-freedom isolation structures, providing a simplified yet accurate means of predicting seismic responses. The reliability of the modified Takeda hysteretic model is verified through comparative analysis with experimental data, providing a solid foundation for the research. Furthermore, a multi-degree-of-freedom shear model is employed for rapid elastic–plastic analysis, validated against finite element software, resulting in an impressive 85% reduction in computation time while maintaining high accuracy. The fragility analysis reveals the staggered upward trend in the vulnerability of the upper structure and isolation layer, highlighting the importance of comprehensive damage control to enhance overall seismic performance.